Does corruption influence the self-restraint attitude of women-led SMEs towards bank lending? - Galli, Emma; Mascia, Danilo Valerio; Rossi, Stefania Patrizia Sonia (Oxford University Press, 2018)
In this article we address the question of whether the perceived level of corruption in a country may influence women’s inclination in self-refraining from applying for bank loans. Using a sample of 60,058 observations—drawn from the European Central Bank- Survey on the Access to Finance of Enterprises (ECB-SAFE)—related to small- and medium- sized enterprises (SMEs) chartered in 11 Euro-area countries during the period 2009–2014, we first investigate whether female-led businesses are more likely, than male-led ones, to refrain from applying for bank credit. Finally, we assess whether corruption actually matters in the women’s decision not to relying on the bank-lending channel. Our results—robust to various model specifications—highlight that women-led SMEs face a higher probability to self-refrain from applying for loans vis-à-vis their male counterparts. In addition, although corruption appears strongly correlated to the self-restraint attitudes of firms, our empirical analysis reveals that women-led SMEs generally tend to refrain from applying for loans, more than men, regardless of the quality of the surrounding environment.